2/3(6x-12x)=4x+12

Simple and best practice solution for 2/3(6x-12x)=4x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/3(6x-12x)=4x+12 equation:



2/3(6x-12x)=4x+12
We move all terms to the left:
2/3(6x-12x)-(4x+12)=0
Domain of the equation: 3(6x-12x)!=0
x∈R
We add all the numbers together, and all the variables
2/3(-6x)-(4x+12)=0
We get rid of parentheses
2/3(-6x)-4x-12=0
We multiply all the terms by the denominator
-4x*3(-6x)-12*3(-6x)+2=0
Wy multiply elements
-12x^2(--36x(-+2=0
We use the square of the difference formula
-12x^2(+36x(-2=0

See similar equations:

| y-25=-13 | | 7(x+5)=7(x-4) | | 3xˆ2+18x+27=0 | | 29=6p-19 | | -5(x+3)=-5 | | H(t)=-16^2+58t+3 | | -2+4y=6 | | 6)t+5)=-36 | | u-2=8 | | 5​z​​4​​=​5​​12​​ | | 15+w=20 | | 7(v-1)-7=-4(-5v+5)-3v | | 4(y-9)=8(y=3) | | -9(x-4)=-(x+20) | | -6(x+7)=-24 | | .91x=x-4 | | 3x^2+2=-10 | | 7b-3=4(2-b) | | 32-5x=16+11x | | 13x-10x-7=2 | | y^2-X^2=175 | | 7x-16=-12 | | 2x+33+7=x+28 | | 1/4x=7/4x-9/8 | | 3u-27=-5(u+7) | | 14n+77n=-35 | | 2x2-x-6=0 | | R(x)=-0.1(2000)^2+30(2000) | | 5x+8x–2x=50 | | R(x)=-0.1x^2+30x | | 12(x−32)=2+5x | | P(x)=x^2-25x+5000 |

Equations solver categories